Injectable organic-inorganic hybrid hydrogels for bone defect repair - Zhang, Huan; Ding, Shuo; Xue, Huai; Wang, Shuguang; Quan, Xiaoyu; Zhang, Dong; Liu, Xiao; Tang, Hai (Frontiers in Bioengineering and Biotechnology, 2025)
Bone defects caused by trauma, tumor resection, and surgery present significant clinical challenges, often resulting in complications such as delayed union, nonunion, and even long-term functional impairment. Current treatments, including autografts and allografts, are limited by donor site morbidity, immune rejection, and pathogen transmission, highlighting the need for developing reliable synthetic alternatives. To address these challenges, we report a binary composite hydrogel combining gelatin methacryloyl (GelMA) and κ-Carrageenan, reinforced with calcium phosphate cements (CPC). GelMA ensures rapid gelation and biocompatibility, κ-carrageenan improves injectability, and CPC enhances mechanical strength and osteogenic activity, collectively creating a robust and versatile hydrogel system. Furthermore, the hydrogel’s injectable, adaptive, and self-healing characteristics enable it to conform to irregular bone defect sites, providing mechanical support and osteogenic stimulation. It also releases bioactive components to accelerate bone regeneration. With exceptional toughness and resilience, this hydrogel recovers its shape after deformation, positioning it as a promising candidate for clinical bone defect repair applications.